Surface modification of carbon dots by UV laser radiation. Issue 1 (April 2021) - Stepanova, M; Dubavik, A; Skurlov, I; Zakharov, V; Rogach, A
Abstract: Carbon dots have been modified using UV irradiation (405 nm laser light). UV irradiation of carbon dots has led to various changes in optical properties, which in turn means photomodification of the carbon dots surface. With an increase in light transmission, we have obtained the increasing intensity of photoluminescence and a blue shift by the laser irradiation of the carbon dots. The proposed method can help to adapt and improve the optical properties of carbon dots and can be used in applications, for example, in the optical encryption field.